Deciphering Paleoceanographic Shifts Inferred from the Foraminiferal Record of the Western Svalbard Slope (Bellsund Drift) over the Past Century - Gamboa Sojo, Viviana M.; Morigi, Caterina; Langone, Leonardo; Lucchi, Renata G. (Journal of marine science and engineering, 2024)
The objective of this study was to reconstruct the last century’s climatic oscillations in the Arctic region around the Fram Strait using high-resolution analysis of foraminiferal assemblages as proxies for surface and deep-water mass properties. In this area, warm Atlantic water masses are advected to the Arctic Ocean through the West Spitsbergen Current, representing the northernmost tip of the Global Thermohaline Circulation. The interaction between the cold Arctic and the warm Atlantic water masses significantly influences the entire foraminiferal community. Planktic species such as Neogloboquadrina pachyderma and Turborotalita quinqueloba are respectively used as indicators of cold Arctic water and warm Atlantic water masses. Among the main benthic species, Cibicidoides wuellerstorfi, Epistominella exigua, and Oridorsalis tener stand out, serving as proxies for the bottom water mass current velocity and paleoproductivity. The paleoenvironmental reconstruction obtained with the foraminiferal assemblages, together with data from satellite monitoring of the sea ice extent and the long-term record of the annual temperature of the West Spitsbergen Current measured over the last 50 years, support the evidence of a progressively rising heat influx into the Arctic Ocean due to an increasing Atlantic water inflow, forcing the consequent decay of the sea ice extent.